Class, Politics and Social Change: The Remaking of the Working Class in 1940s Canada - Camfield, David (York University, 2002)
This interdisciplinary dissertation aims to develop social and political theory capable of understanding social class as a structured process and relationship mediated by gender, race and other social relations and taking place in time and specific socio-material contexts, in order to analyse working classes as historical formations. It also aims to use this perspective and the existing body of historical scholarship to conduct a theoretically-rigorous study of the remaking of the Canadian working class in the 1940s. Arguing that recent theoretical work on class formation is inadequate, the dissertation critically appropriates ideas drawn from classical and contemporary scholarship to outline a theory of working classes as historical formations. An account of how dominant classes exercise power in capitalist societies is a necessary complement to this theory; the overview developed theorizes the existence of capitalist rule in differentiated forms and as inherently, but not primarily, ideological. From this perspective, the dissertation analyses the remaking of the Canadian working class in the paid workplace, community and household spheres in the 1940s. It argues that between 1941 and 1947 a broad but uneven process of class recomposition took place, focussing on such issues as the character of struggles in this period, their participants, their organizations and ideologies in order to illuminate the dynamics of change in working-class formations. In the course of struggle, both the working-class formation and capitalist rule were altered in important ways. The new formation that stabilized in the late 1940s featured improved living standards and greater unity against capital at the most elementary level. It was also shaped in important respects by a particular configuration of racist, sexist and heterosexist social relations. Unions changed from within and without, becoming generally committed to a responsible and bureaucratic practice. The CCF became the undisputed party of the English-Canadian workers' movement, weakening and marginalizing political radicalism. Although it is misleading to interpret this as working-class incorporation, working-class capacities to change society had been constrained and undermined in new ways, in part as a result of the very reforms workers wrested from employers and state power.